2012
DOI: 10.1021/ja3047415
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Carbon–Carbon σ-Bond Hydrogenation with Water Catalyzed by Rhodium Porphyrins

Abstract: The catalytic carbon-carbon σ-bond activation and hydrogenation of [2.2]paracyclophane with water in a neutral reaction medium is demonstrated. The hydrogen from water is transferred to the hydrocarbon to furnish hydrogen enrichment in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 37 publications
(19 reference statements)
0
19
0
1
Order By: Relevance
“…47 Similar chemistry was developed by the group previously in the context of C–C activation using stoichiometric rhodium phorphyrin complexes. 48,49 In this transformation, PCP is catalytically converted to 4,4′-dimethyl-bibenzyl 113 under two possible conditions (eqn (29)).…”
Section: Catalytic C–c Activation Without Chelationmentioning
confidence: 89%
“…47 Similar chemistry was developed by the group previously in the context of C–C activation using stoichiometric rhodium phorphyrin complexes. 48,49 In this transformation, PCP is catalytically converted to 4,4′-dimethyl-bibenzyl 113 under two possible conditions (eqn (29)).…”
Section: Catalytic C–c Activation Without Chelationmentioning
confidence: 89%
“…37 The literature precedent for C-C bond scission primarily relies on the assistance of transition metal catalysts, high hydrogen pressure, elevated temperatures, or a combination of all three parameters. [38][39][40][41][42][43][44] Therefore, unexpected C-C bond cleavage (discovered from photophysical studies of alignment of electron donor (corannulene) and acceptor (7,7,8,TCNQ) in the solid state) reported herein led us to probe mechanistic pathways to determine the feasibility for p-bowl planarization and factors that could affect such a transformation including strain energy (E s ) and released energy (E 0 , Scheme 1, see more details in the ESI †). The electron coupling and charge transfer (CT) rates between "open" corannulene (or parent corannulene) and TCNQ were evaluated by applying Marcus theory.…”
Section: Introductionmentioning
confidence: 86%
“…PCP was catalytically hydrogenated with H 2 O to give 79 % yield of 4,4,′‐dimethylbibenzyl 54 catalyzed by 10 mol‐% of Rh III (ttp)H (Table , entry 2). [41a] The catalytic transfer hydrogenation protocol is applicable with to Ir III (ttp)H catalyst as well (Table , entry 3). [41b] The stoichiometric reaction of Rh II (tmp) 48 with PCP resulted in the exclusive cleavage of the benzylic C–C bond to yield the di‐rhodium benzylic product 56 in 85 % yield (Scheme ).…”
Section: C–c Bond Activation With Group 9 Metal Porphyrin Complexesmentioning
confidence: 99%
“…[41a] The catalytic transfer hydrogenation protocol is applicable with to Ir III (ttp)H catalyst as well (Table , entry 3). [41b] The stoichiometric reaction of Rh II (tmp) 48 with PCP resulted in the exclusive cleavage of the benzylic C–C bond to yield the di‐rhodium benzylic product 56 in 85 % yield (Scheme ). Kinetic studies showed that the CCA reaction is second order on Rh II (tmp) and first order on PCP.…”
Section: C–c Bond Activation With Group 9 Metal Porphyrin Complexesmentioning
confidence: 99%
See 1 more Smart Citation